Molecular Basis for the Interaction of Low Density Lipoprotein Receptor-related Protein 1 (LRP1) with Integrin α(M)β(2): IDENTIFICATION OF BINDING SITES WITHIN α(M)β(2) FOR LRP1 - Ranganathan, Sripriya (American Society for Biochemistry and Molecular Biology, 2011)
The LDL receptor-related protein 1 (LRP1) is a large endocytic receptor that controls macrophage migration in part by interacting with β(2) integrin receptors. However, the molecular mechanism underlying LRP1 integrin recognition is poorly understood. Here, we report that LRP1 specifically recognizes α(M)β(2) but not its homologous receptor α(L)β(2). The interaction between these two cellular receptors in macrophages is significantly enhanced upon α(M)β(2) activation by LPS and is mediated by multiple regions in both LRP1 and α(M)β(2). Specifically, we find that both the heavy and light chains of LRP1 are involved in α(M)β(2) binding. Within the heavy chain, the binding is mediated primarily via the second and fourth ligand binding repeats. For α(M)β(2), we find that the α(M)-I domain represents a major LRP1 recognition site. Indeed, substitution of the I domain of the α(L)β(2) receptor with that of α(M) confers the α(L)β(2) receptor with the ability to interact with LRP1. Furthermore, we show that residues (160)EQLKKSKTL(170) within the α(M)-I domain represent a major LRP1 recognition site. Given that perturbation of this specific sequence leads to altered adhesive activity of α(M)β(2), our finding suggests that binding of LRP1 to α(M)β(2) could alter integrin function. Indeed, we further demonstrate that the soluble form of LRP1 (sLRP1) inhibits α(M)β(2)-mediated adhesion of cells to fibrinogen. These studies suggest that sLRP1 may attenuate inflammation by modulating integrin function.